SECURITIZATION IN THE PHILIPPINES’ DRUG WAR: DISCLOSING THE POWER-RELATIONS BETWEEN DUTERTE, FILIPINO MIDDLE CLASS, AND THE URBAN POOR: Disclosing the Power-Relations between Duterte, Filipino Middle Class, and the Urban Poor - Muhammad Anugrah Utama (Indonesian Journal of International Relations, 2021)
Since his inauguration in late June 2016, Duterte has adopted “shoot-to-kill” policy for suspected criminals and drug addicts. Despite public support, the policy received growing international backlash over extra-judicial killing and mass slaughter of youth, mainly the urban poor communities. This paper attempts to analyze the process of securitization waged by President Duterte to construct a state of emergency of drugs so that extraordinary yet outrageous measures can be justified by using the Copenhagen School’s securitization concept developed by Buzan, Waever, and Wilde (1998). This paper argues that President Duterte’s speech acts and politicization of threats successfully build public support of harsher law enforcement on drug-related crime. Furthermore, the paper also connects the dot between the securitization of drugs as Duterte’s political weapon and the disproportionate impact it has on the minority poor and vulnerable children. Using the critical application of securitization theory developed by Charett (2009), the paper concludes that the asymmetrical power relations will lead to securitizing actor maintaining its power in the expense of oppressing the marginalized voice, especially the minority poor and children population, thus de-securitization model (Hansen, 2012) is more effective in dealing drug-related crimes in the Philippines.